Characterization and Fabrication of Nanocomposite Thin Films of PANI Embedded with Ag-Mn Alloy for E. coli Sensor. (2016) - Abdullah, Huda; Naim, Norshafadzila Mohammad; Hamid, Aidil Abdul; Umar, Akrajas Ali
Abstract: We presented a simple method of prototype E. coli sensor based on polyaniline with Ag-Mn nanocomposite thin films. The nanocomposite of PANI and bimetallic nanoparticles of silver and manganese were prepared by sol-gel method. XRD analysis shows the crystallite face-centered cubic structure of Ag-Mn. The crystallite sizes increase with the increment of Mn concentrations. UV-Vis absorption spectra show the maximum peaks at 428 nm – 438 nm. FESEM image shows the nanospherical Ag-Mn alloy particles are in diameter range of 13 nm – 42 nm. The sensor performance of PANI-Ag-Mn nanocomposite thin films upon E. coli bacteria indicates the sensitivity increases when Mn concentration was decreased.